Physiological studies on chemically induced systemic resistance against charcoal rot disease in sunflower plant - Ahmed Mahmoud Saleh Mohamed; Mahmoud M. A. Gabr; Shahnaz A. M. Alwakeel; Walid M. Abuelsoud (Cairo : Ahmed Mahmoud Saleh Mohamed, 2010)
Induction of systemic resistance to charcoal rot disease caused by Macrophomina phaseolina ( Tassi ) Goidanich in sunflower ( Helianthus annuns L. ) was studied after priming the seeds with salicylic acid ( SA ) and coumarin ( COU ) at three different levels ( 0.3 , 1.0 and 3.0 mM ) under greenhouse conditions . Treatments of sunflower seeds with SA or COU significatly decreased disease severity and improved the host plant growth
Thesis (Ph.D.) - Cairo University - Faculty of Science - Department of Botany-Physiology
Issued also as CD
Keywords: M.Phaseolina; Salicylic acid; Sunflower